Akses Informasi Publik Sebagai Kunci Pemberdayaan Perempuan Di Komunitas Lokal - Rinawati (LPPM Universitas Ekasakti, 2024)
Access to public information plays a strategic role in empowering women, particularly in local communities that often face structural barriers in education, economy, and healthcare. This study aims to understand how access to information can empower women to enhance their participation in decision-making at the community level. Using a qualitative descriptive approach, the research was conducted in Koto Tangah District, Padang City. The results show that public information positively contributes to the improvement of women's literacy on climate change adaptation, urban farming, and disaster preparedness. Identified barriers include limited digital literacy and the lack of gender-responsive policies. The study recommends strengthening gender-friendly information infrastructure and promoting more active involvement of women in local policy planning.